Ultra-selective molecular-sieving gas separation membranes enabled by multi-covalent-crosslinking of microporous polymer blends - Xiuling Chen; Yanfang Fan; Lei Wu; Linzhou Zhang; Dong Guan; Canghai Ma; Nanwen Li (Nature Communications, 2021)
Microporous polymers become increasingly attractive as materials for the fabrication of permeable and selective gas separation membranes but separation performance is often limited by broad pore size distribution. Here, the authors design a porous polymer membrane via multi-crosslinking of miscible blends of microporous polymers enabling simultaneous high permeability and selectivity.